Shaping our Minds: Stem and Progenitor Cell Diversity in the Mammalian Neocortex - Franco, Santos J. (2013)
The neural circuits of the mammalian neocortex are crucial for perception, complex thought, cognition and consciousness. This circuitry is assembled from many different neuronal subtypes with divergent properties and functions. Here, we review recent studies that have begun to clarify the mechanisms of cell-type specification in the neocortex, focusing on the lineage relationships between neocortical progenitors and subclasses of excitatory projection neurons. These studies reveal an unanticipated diversity in the progenitor pool that requires a revised view of prevailing models of cell-type specification in the neocortex. We propose a “sequential progenitor-diversification model” that integrates current knowledge to explain how projection neuron diversity is achieved by mechanisms acting on proliferating progenitors and their postmitotic offspring. We discuss the implications of this model for our understanding of brain evolution and pathological states of the neocortex.